Negative interest rates, excess liquidity and retail deposits: Banks' reaction to unconventional monetary policy in the euro area - Selva Demiralp; Jens Eisenschmidt; Thomas Vlassopoulos (European Central Bank (ECB), 2019)
Negative monetary policy rates are associated with a particular friction because the remuneration of retail deposits tends to be floored at zero. We investigate whether this friction affects banks' reactions when the policy rate is lowered to negative levels, compared to a standard rate cut in the euro area. We exploit the cross-sectional variation in banks' funding structures jointly with that in their excess liquidity holdings. We find evidence that banks highly exposed to the policy tend to grant more loans. This confirms studies that point to higher risk taking by banks as a reaction to negative rates. It, however, contrasts some earlier research associating negative rates with a contraction in loans. We illustrate that the difference is likely driven by the broader coverage of our loan data, longer time span of our sample and, importantly, the explicit consideration of the role of excess liquidity in our analysis.
Keywords: E43; E52; G11; G21; 330; negative rates; bank balance sheets; transmission mechanism